Hubungan Antara Kompensasi, Keterlibatan Karyawan, dan Kinerja Organisasi - John Sihar Manurung; Muhammad Fatkhurohman Albashori; Putri Hartati; Ahmad Salabi; Latifah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to determine and analyze the relationship between peace, employee engagement, and organizational performance. This research approach collects data through literature studies, which involve reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this study are The relationship between peace, employee engagement, and organizational performance is very important in the world of work. Because the desire to be able to increase employee engagement, employees who feel motivated tend to be more committed and involved. Engaged employees are more motivated to work hard in helping to achieve organizational goals, which in turn will improve organizational performance. Therefore, to achieve the best results, a balance is needed between peace, employee engagement, and organizational performance. Because the three elements influence each other in creating a productive and successful work environment.